Chinese Emigration to Australia around 1900: A Re-examination of Australia’s ‘Great White Walls’ - Taylor, Antony (History compass, 2013)
This article reassesses the debates around Chinese emigration into the Australian colonies before Federation in 1901. Drawing on the literature relating to the emergence of the Chinese community in Australia, it argues that pressures exerted by anti-Chinese organisations that thrived following the expansion of representative democracy in the Australian colonies, and the emergence of organised labour parties, were instrumental in the creation of exclusionary campaigns waged against Chinese migrants. By depicting the Chinese as temperamentally unsuited to democracy and through campaigns to highlight the impact of imported, low cost manual workers into the Australian colonies, the new forces of colonial labour led by radical politicians were at the heart of an attempt to erect ‘White Walls’ against migrants from South-East and East Asia. These campaigns drew on a fund of images and popular fears that cohered around the role of the opium den, and the solitary, itinerant Chinese male.